Bank Stock Returns in Responding the Contribution of Fundamental and Macroeconomic Effects - Nurazi, Ridwan; Usman, Berto (Semarang State University, 2016)
This study attempts to examine the effect of financial fundamentals information using CAMELS ratios and macroeconomics variables surrogated by interest rate, exchange rate, and inflation rate toward stock return. By employing panel data analysis (Pooled Least Squared Model), the results reveal that several financial ratios perform a bit contrary to the theory, in which the ratio of CAR shows positive sign but insignificantly contributes to stock returns. Also, the ratio of NPL does not affect the return. In fact, ROE and LDR positively and significantly contribute toward banksâ stock return. Meanwhile, NIM and BOPO show negative signs. The other macroeconomic variables, interest rate (IR), exchange rate (ER) and inflation rate (INF) are consistent with the a priori expectation, in which those variables negatively and significantly contribute to stock return of 16 banks, for the observation period from 2002 to 2011 in the Indonesian banking sector.